BMP2-Functionalized Biomimetic Calcium Phosphate Graft Promotes Alveolar Defect Healing During Orthodontic Tooth Movement in Beagle Dogs - Jiang, Shijie; Liu, Tie; Wu, Gang; Li, Wen; Feng, Xiaoxia; Pathak, Janak L.; Shi, Jiejun (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Grafting of biomaterial in alveolar defect facilitates bone healing and orthodontic treatment. BMP2-functionalized biomimetic calcium phosphate (BioCaP) graft had shown excellent bone defect healing potential in many preclinical studies. In this study, we aimed to investigate the influence of BioCaP graft on surgical alveolar bone defect healing during orthodontic tooth movement (OTM) in beagle dogs. Methods: Nine Beagle dogs were randomly assigned to three groups: control, deproteinized bovine bone (DBB), and BioCaP. The maxillary second premolars were protracted into the defects of the extracted maxillary first premolar for 8 weeks. The rate of OTM, alveolar remodeling and bone defect healing were evaluated by histology, histomorphometry, and cone beam computed tomography (CBCT) imaging. Periodontal probing depth was analyzed. Gingival cervicular fluid was collected at week 4 and 8, and the IL-1β level was measured by ELISA. Results: The histological sections of the bone defect showed more newly formed bone in the BioCaP group. The percentage of new bone formation in the BioCaP group was 1.61-, and 1.25-fold higher compared to the control and DBB group, respectively. After 8 weeks of OTM, the resorption rate of BioCaP was 1.42-fold higher compared to DBB. The root resorption index in the DBB group was 1.87-, and 1.39-fold higher compared to the control and BioCaP group, respectively. CBCT images showed 1.92-, and 1.36-fold higher bone mineral density in the BioCaP group compared to the control and DBB group, respectively. There was no significant difference in OTM among the three groups. The distance between the enamel cementum and the crest of the alveolar ridge in the control group was 1.45-, and 1.69-fold higher compared to DBB and BioCaP group, respectively. Periodontal probing depth at week 8 was reduced in the BioCaP group compared to the control. IL-1β concentration in the gingival cervicular fluid was significantly lower in the BioCaP group compared to the control group at week 4 and 8. Conclusion: BioCaP graft robustly promoted bone regeneration and alveolar bone defect healing without affecting OTM. BioCaP graft caused less alveolar bone recession and root resorption of traction tooth with favorable periodontal attachment level indicating that BioCaP as a bioactive and functional bone filling material for alveolar bone defects during orthodontic treatment.